2023
DOI: 10.1021/acschemneuro.3c00223
|View full text |Cite
|
Sign up to set email alerts
|

Altered Secretion, Constitution, and Functional Properties of the Gastrointestinal Mucus in a Rat Model of Sporadic Alzheimer’s Disease

Abstract: The gastrointestinal (GI) system is affected in Alzheimer's disease (AD); however, it is currently unknown whether GI alterations arise as a consequence of central nervous system (CNS) pathology or play a causal role in the pathogenesis. GI mucus is a possible mediator of GI dyshomeostasis in neurological disorders as the CNS controls mucus production and secretion via the efferent arm of the brain−gut axis. The aim was to use a brain-first model of sporadic AD induced by intracerebroventricular streptozotocin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 70 publications
2
16
0
Order By: Relevance
“…Previous experiments have revealed that duodenal goblet cells in the STZ-icv rat model of AD do not respond to cholinergic stimulation for mucus secretion . This study builds upon those findings by demonstrating that the GI tracts in STZ-icv rats also exhibit reduced responsiveness to an oxidative environment and exposure to D-galactose.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Previous experiments have revealed that duodenal goblet cells in the STZ-icv rat model of AD do not respond to cholinergic stimulation for mucus secretion . This study builds upon those findings by demonstrating that the GI tracts in STZ-icv rats also exhibit reduced responsiveness to an oxidative environment and exposure to D-galactose.…”
Section: Discussionsupporting
confidence: 63%
“…In transgenic animal models of AD, it is common to observe physiological changes in the GI tract before observing any pathological changes in the brain. This sequence of events makes it difficult to study the GI consequences of localized neurodegeneration in the CNS. On the other hand, brain-first nontransgenic animal models, which involve the targeted delivery of toxic substances (e.g., amyloid β, streptozotocin (STZ), colchicine, and okadaic acid) that mimic AD-related neuropathology to the CNS, provide an opportunity to investigate the one-way disruption of the gut–brain axis. These models offer invaluable insights into how localized neurodegeneration impacts the structural and functional integrity of the gut. One of the most extensively studied and well-established brain-first models of sporadic AD is the rat model generated by intracerebroventricular administration of the diabetogenic toxin streptozotocin (STZ-icv). , Based on the evidence accumulated over the last 30 years, the STZ-icv model recapitulates key behavioral and neuropathological hallmarks of AD .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABTS (7 mM) was incubated with K 2 S 2 O 8 (2.45 mM) for 24 h. ABTS/K 2 S 2 O 8 solution was diluted 40-fold and incubated with 1 μL of each homogenate in a volumetric ratio of 1:100 (sample/ABTS). The absorbance at 405 nm was measured after 5 min using an Infinite F200 PRO multimodal microplate reader (Tecan, Switzerland) . The difference between the baseline control solution (ABTS) and final absorbance was proportional to the sample antioxidant capacity .…”
Section: Methodsmentioning
confidence: 99%
“…Accumulating evidence suggests that the gut might play an important role in the etiopathogenesis and progression of Alzheimer’s disease (AD). , Gastrointestinal (GI) alterations have been reported in both transgenic and nontransgenic animal models of AD. Importantly, GI alterations often precede neuropathological changes in the brain and correlate with disease progression, , suggesting that pathophysiological processes in the gut might contribute to dyshomeostasis in the central nervous system (CNS) in the early stages of neurodegeneration. Honarpisheh et al reported that GI dysfunction takes place before the onset of cognitive symptoms and the accumulation of cerebral amyloid-β (Aβ) in the (6 months old) Tg2576 mouse model of familial AD .…”
Section: Introductionmentioning
confidence: 99%